Beyond user experience of cloud service: Implication for value sensitive approach. Issue 1 (February 2015) - Shin, Donghee
Highlights An acceptance model of cloud computing. The perceived features of cloud services. Human values are explored. How designers should take these values into account is examined. The significant antecedents of cloud computing.